Penggunaan slow sand filter dalam pengolahan air gambut untuk menurunkan turbiditas dan kandungan senyawa organik - Utami Irawati; Nugi Maulana; Tety Wahyuningsih Manurung (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
Slow Sand Filter (SSF) is a simple technology to improve water quality. In this research, the effect of retention time and filter age towards the effectivity of SSF in decreasing turbidity and organic content in peat water was investigated. Another filter using commercial activated carbon was also used to treat the peat water samples as a comparison. The results of this study shows that retention time affects the effectivity of SSF and activated carbon in decreasing turbidity and organic contents. Activated carbon needed a lower retention time to give an optimal turbidity decrease compared to SSF. While activated carbon needed 2 hours of retention time to give an optimum result in decreasing turbidity, SSF needed at least 3 hours of retention time. Retention time appeared to also significantly affect the decrease in organic content. This is probably due to the life cycle of the bacteria living in the SSF and the time it took to have a sorption equilibrium in the activated carbon filter. The age of the filter also signifcantly affects the performance of SSF, in which older filter gave better results in removing organic content in peat water